Deciphering the Intercellular Communication Network of Peripartum Decidua that Orchestrates Delivery - Huang, Jingrui; Zhang, Weishe; Zhao, Yanhua; Li, Jingzhi; Xie, Mingkun; Lu, Yang; Peng, Qiaozhen; Zhang, Jiejie; Li, Ping; Dai, Lei (Frontiers in Cell and Developmental Biology, 2021)
Intercellular communication in the decidua plays important roles in relaying information between the maternal and fetal systems in the maintenance of pregnancy and the transition to labor. To date, several studies have explored cell-cell communications in the decidua during different periods of pregnancy, but studies systematically decoding the intercellular communication network, its internal cascades, and their involvement in labor are still lacking. In this study, we reconstructed a decidua cell-cell communication network based on scRNA-seq of peripartum decidua via the CellCall method. The results showed that endometrial cells (EECs) and extravillous trophoblasts relayed most of the common intercellular signals in the decidua both before delivery (DBD) and after delivery (DAD). Endothelial cells and EECs controlled many WNT-signaling-related intercellular communication factors that differed between DBD and DAD, some of which could be candidate biomarkers for the diagnosis of labor. Analysis of intercellular communications related to T cells identified abundant maternal-fetal immune-tolerance-related communication, such as TNFSF14-TNFRSF14/LTBR and FASLG-FAS signaling. We further explored the characteristics of the B cell receptor (BCR) and T cell receptor (TCR) repertoires by single-cell BCR/TCR sequencing. The results showed no significant differences in clonal expansion of B/T cells between DAD and DBD, indicating there was no significant change to adaptive immunity at the maternal-fetal interface during delivery. In summary, the findings provide a comprehensive view of the intercellular communication landscape in the peripartum decidua and identified some key intercellular communications involved in labor and maternal-fetal immune tolerance. We believe that our study provides valuable clues for understanding the mechanisms of pregnancy and provides possible diagnostic strategies for the onset of labor.